2023
DOI: 10.1186/s12974-023-02707-y
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin-induced inhibition of Wnt/β-catenin signaling in dendritic cells promotes an autoimmune response in experimental autoimmune uveitis

Abstract: Background Previous reports have indicated that disrupting the Wnt/β-catenin pathway in dendritic cells (DCs) may affect the progression of autoimmune inflammation; however, the factors and timing that regulate Wnt/β-catenin signaling have not been clearly understood. Methods Experimental autoimmune uveitis (EAU) mice and Vogt–Koyanagi–Harada disease (VKH) patient samples were used to detect the expression of Wnt/β-catenin pathway genes. Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Although the etiology and pathogenesis of VKH disease remain unclear, it has been reported to be related to genetic and immunological factors. [ 18 ] Previous genetic studies have found several genes associated with VKH disease, including IL23R‐C1orf141, ADO‐ZNF365‐EGR2, IL17F, CTLA4, and MIF. [ 19 , 20 , 21 , 22 ] Human leukocyte antigens (HLAs), such as HLA‐DRB1 * 0405, DRB1 * 0401, and HLA‐B * 51, are strongly associated with VKH disease or Behcet's disease in various ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiology and pathogenesis of VKH disease remain unclear, it has been reported to be related to genetic and immunological factors. [ 18 ] Previous genetic studies have found several genes associated with VKH disease, including IL23R‐C1orf141, ADO‐ZNF365‐EGR2, IL17F, CTLA4, and MIF. [ 19 , 20 , 21 , 22 ] Human leukocyte antigens (HLAs), such as HLA‐DRB1 * 0405, DRB1 * 0401, and HLA‐B * 51, are strongly associated with VKH disease or Behcet's disease in various ethnic populations.…”
Section: Introductionmentioning
confidence: 99%